The trade off - Jones, Sandie (Minotaur Books, 2023)
"For Stella, deputy editor of The Globe, the choice has always been clear. It doesn't matter how low she has to stoop--getting the best story is what she's built her reputation on. For Jess, The Globe's rookie reporter, the story stops when the truth does. But she knows that the dirty tricks of the tabloids will be hard to overturn. And when a celebrity is hounded by The Globe and pays the ultimate price, Jess wonders just how much Stella and the paper are responsible. Determined to show the world what the tabloid is capable of, Jess will do whatever it takes to uncover the truth, but she needs to watch her back, because someone else is prepared to kill to bury it."--